Investigation of Bi2MoO6/MXene nanostructured composites for photodegradation and advanced energy storage applications - Sagarika Panda; Savita Mehlawat; Neeraj Dhariwal; Preety Yadav; Vinod Kumar; O. P. Thakur; Neha V. Brahmankar; Santosh J. Uke; Ashwani Kumar; Amit Sanger (Scientific Reports)
Abstract This study presents nanostructured composite Bi2MoO6/MXene heterostructure by using hydrothermal method for photodegradation of the congo-red dye and also for energy storage devices. X-ray diffractometer (XRD), High Resolution Transmission Electron Microscopy (HRTEM), Field emission scanning electron microscope (FESEM) and X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller (BET) were performed to examine the structural properties along with surface area and porosity of the material. Due to addition of MXene the larger surface area and improved pore size help to quickly break down additional organic pollutants by adsorbing them. The band gap of Bi2MoO6/MXene nanostructured composite reduced to 2.4 eV suggesting transfer of electrons from VB to CB. Bi2MoO6/MXene exhibits a high (92.3%) photocatalytic degradation rate for a duration of 16 min which was verified using UV-visible spectroscopy, also scavenger test was conducted to ascertain the reactive agent along with the degradation pathway was confirmed by LCMS. Elemental content was also established by using inductively coupled plasma mass spectrometry (ICP-MS). For estimating energy storage capacity cyclic voltammetry (CV) was performed. It was observed Bi2MoO6/MXene nanostructured composite electrodes had specific capacitance of 642.91Fg− 1, power density of 1.24 kWkg− 1, and energy density of 22.32 Whkg− 1 at a current density of 5Ag− 1 also it exhibited 64.42% capacity retention having current density 20 Ag− 1 throughout 10,000 Galvanostatic charge discharge (GCD) cycles. High electrical conductivity of Bi2MoO6/MXene electrode was again examined by Electrochemical impedance spectroscopy (EIS). These findings demonstrate the potential of Bi2MoO6/MXene nanostructured composites in both photodegradation and energy storage applications.